PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA MIND MAPPING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN TEKS EKSPLANASI SISWA KELAS V SEKOLAH DASAR - Puspita, Della; Syarif, Ahmad; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to address the low reading comprehension ability of fifth-grade students in understanding explanatory texts. The research aimed to examine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by Mind Mapping media on students’ reading comprehension skills. A quantitative approach with a pre-experimental design employing one-group pretest–posttest was used. The participants consisted of 19 fifth-grade students of SDN 12/I Terusan in the 2025/2026 academic year. Data were collected using an objective multiple-choice test that had been validated and tested for reliability prior to implementation. The data analysis involved descriptive statistics, normality testing using the Shapiro–Wilk test, and hypothesis testing through a paired sample t-test. The results showed that the pretest and posttest data were normally distributed. The average pretest score was 42.10, indicating low reading comprehension ability, while the average posttest score increased to 76.14 after the implementation of the CIRC model assisted by Mind Mapping. The paired sample t-test results indicated a significance value of 0.000, which was lower than the significance level of 0.05, leading to the rejection of the null hypothesis. These findings demonstrate that the implementation of the Cooperative Integrated Reading and Composition (CIRC) model assisted by Mind Mapping media has a significant positive effect on improving students’ reading comprehension of explanatory texts. The learning model also encouraged active participation and collaborative learning, contributing to a more meaningful reading comprehension process.